KERAGAAN KESEMPATAN KERJA DI SKTOR PERTANIAN DAN PENGARUHNYA TERHADAP PENDAPATAN RUMAH TANGGA PEDESAAN - ZAKARIA, AMAR K. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 2 Juli 2006)
The Performance of Labor Opportunity on Agriculture Sector Toward Rural Household to Increase of Income Effects. The study had done on July, 2005 in Tarusa and Kalabeso villages, Sumbawa district, West Nusa Tenggara. In general, this study aim’s to observe degrees of labor on several of farming activities and farmer’s income. The research using descriptive methods with explanatory analysis to prepare cross table. Primary data were collected from 60 farmers with direct interview. The result of study showed that degrees of family labor on farming activities were reached 47 – 56 percent from totally of labor use. While the farming on low land was reached 39 – 46 percent using family labor, upland farming (41 – 53%), estate farming (42 – 52%) and livestock (100%). Based on totally of income of farmer’s household from agricultural had biggest contribution, there are 79 – 87 percent.
Keywords: Farming, Household, Income, Labor.